Meeting the southern brothers: a revision of the Neotropical spider genus Hexapopha Platnick, Berniker & Víquez, 2014 (Araneae, Oonopidae) - Feitosa, Níthomas M.; Ott, Ricardo; Bonaldo, Alexandre B. (Zootaxa, 2023)
The goblin spider genus Hexapopha Platnick, Berniker & Víquez, 2014 is revised. The four Costa Rican species recognized in the original description of the genus are re-diagnosed: H. reimoseri (Fage, 1938) (the type species), H. hone Platnick, Berniker & Víquez, 2014, H. osa Platnick, Berniker & Víquez, 2014 and H. jimenez Platnick, Berniker & Víquez, 2014. Two species recently transferred from Gamasomorpha Karsch, 1881 are redescribed: H. brasiliana (Bristowe, 1938), from southern Brazil, of which the male is described for the first time, and H. m-scripta (Birabén, 1954), from Argentina. Thirty-five new species are described from South America, elevating the total number of species to forty-one. Thirty three species are described from Brazil: H. una (♂, ♀), H. brescoviti (♂), H. peba (♂,♀), H. harveyi (♂,♀), H. fannesi (♂), H. erebai (♂), H. periclitata (♂,♀), H. delta (♂), H. tallitae (♂,♀), H. platnicki (♂,♀), H. santosi (♂,♀), H. rheimsae (♂), H. wangi (♂,♀), H. ruizi (♂), H. itabaiana (♂), H. ramirezi (♂), H. depleta (♂), H. gunma (♂), H. corniculata (♂,♀), H. egua (♂), H. izquierdoi (♂,♀), H. numerosa (♂,♀), H. baehrae (♂,♀), H. excavata (♂,♀), H. ubicki (♂,♀), H. quadraginta (♂,♀), H. ilhoa (♂,♀), H. marajoara (♂,♀), H. kropfi (♂,♀), H. caboquinho (♂), H. grismadoi (♂), H. manauara (♂,♀) and H. pantaneira (♂,♀). Two additional new species, H. pithecia (♂,♀) from Peru and H. sorkini (♂,♀) from Venezuela are also described. Species of Hexapopha are restricted to the Neotropical region, from Costa Rica to Northern Argentina. Brazil, where 85% of the species occur, harbors the highest species richness. A key and distribution maps are provided for all species.